Why History Matters for Democracy. Issue 2 (1st December 2019) - Keane, John
Abstract : In this critical commentary, John Keane defends, extends, and reasserts the role of history in democratic theory through an articulation of seven methodological rules: (1) treat the remembrance of things past as vital for democracy's present and future; (2) regard the languages, characters, events, institutions, and effects of democracy as a thoroughly historical way of life and handling of power; (3) pay close attention to the ways in which the narration of the past by historians, leaders, and others is unavoidably a time-bound, historical act; (4) see that the methods that are most suited to writing about the past, present, and future of democracy draw attention to the peculiarity of their own rules of interpretation; (5) acknowledge that, until quite recently, most details of the history of democracy have been recorded by its critics; (6) note that the negative tone of most previous histories of democracy confirms the rule that tales of its past told by historians often harbor the prejudices of the powerful; and (7) admit that the task of thinking about the past, present, and future of democracy is by definition an unending journey. There can be no Grand Theory of Democracy.